Is Training With Gym Machines Safe After Hip Arthroplasty?—An In Vivo Load Investigation - Haffer, Henryk; Bender, Alwina; Krump, Alexander; Hardt, Sebastian; Winkler, Tobias; Damm, Philipp (Frontiers in Bioengineering and Biotechnology, 2022)
Background:Training with gym machines is one of the most popular physical activities after total hip arthroplasty(THA). However, to date, there are no evidence-based recommendations for physical activity after THA, worldwide. The aim of the study is to evaluate the in vivo hip joint loads during exercises on four widely used gym machines in order to provide a source for an evidence-based decision-making process for arthroplasty surgeons. Methods:The in vivo hip joint loads in seven patients (59.6 ±6.4years, 28.6 ±2.1kg/m2) with instrumented hip implants were assessed. The resulting force Fres, bending moment Mbend and torsional moment Mtors were evaluated during the training on leg curl/leg extension machines (loads: 20kg,30kg,40kg), leg press machine (backrest: 10°,30°,60°; load: 50,75,100%BW (bodyweight)) and a rope pull machine (abduction/adduction/flexion/extension; each ipsi- and contralateral;load 10kg). These loads were compared with the loads during walking on treadmill at 4 km/h. Results:In each of the four performed exercises with a total of 23 different load conditions or exercise modes analyzed, a significantly lower or not different load was detected with respect to Fres, Mbend and Mtors measured while walking with 4km/h. Nevertheless, Fres and Mbend demonstrated a trend to increased loading during the ipsilateral monopod standing rope pull exercises hip flexion, extension and abduction. Conclusion:This is the first investigation assessing the in vivo hip joint loads during training on common gym machines. Based on our investigation we assume the investigated gym machines and external loads can be considered mainly as low impact sports (with some exceptions) and thus as safe physical activity after THA.